PRODUKSI BIOGAS DARI AIR LIMBAH INDUSTRI MINYAK KELAPA SAWIT MENGGUNAKAN DIGESTER ANAEROBIK MODIFIKASI DENGAN PENAMBAHAN PENGADUKAN - Aznury, Martha (Politeknik Negeri Sriwijaya, 2018)
Biogas produced from Palm Oil Mill Effluent (POME) can provide several benefits for the environment, such as can reduce environmental pollution and produce new energy sources. The purpose of this research was to determine the ratio of methane was producedfrom batch and fed bacth processes, and to determine the optimal agitation speed for biogas formation from POME as the main ingredient and cow dung as starter. This research used ratio 50:50 of POME:starter and variations of agitation speed are 95 rpm and 100 rpm.Biogas was formed will be taken on days 4th, 8th, 12th, and 16th. The highest yield of biogas by fed batch system was on day 16th with 100 rpm agitation speed produced methane of 9,67%. While the lowest result was on day 4th at 95 rpm agitation speed with 0%. For batch system, thehighest yield of biogas was produced on day 16th at 100 rpm with 7,927%. And the lowest yield was on day 4th at 95 rpm agitation speed with 0,93%. From this reserach, it can be concluded that fed batch system can produce higher methane from the result of the anaerobic fermentation process of POME than batch system. In addition, a higher agitation speed will also produce higher amount of methane